PELESTARIAN NILAI-NILAIBUDAYA PADA KESENIAN KUDA LUMPING DI KECAMATAN TAMBUSAI UTARA - ILHAM RAHMAWATI (Jurnal Budaya Nusantara, 2021)
This research is based on cultural issues. The aims of this research are (1) How to describe the preservation of cultural values ​​in Kuda Lumping art in North Tambusai District. This research is a qualitative research with ethnographic method. The sampling technique in this research is using a proposive sampling technique-nonprobalistic. Data analysis techniques used in this research are data reduction, data presentation, and conclusion drawing. The results of the study show that in Kuda Lumping art there are cultural values ​​that can be used as guidelines and references in people's lives including religious values, mutual cooperation values, responsibility values, unity values, ethical values, solidarity values ​​(togetherness), and aesthetic values. (beauty).